The Use of Quizizz Application on Islamic Education (PAI) Learning in the New Normal Era - Hanif, Muh.; Ningamah, Binti Rofingatun; Izzah, Farah Nuril; Wahyuning, Pangesti; Khasanah, Riana Khomsatun (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
Limited face-to-face is a newly used learning system in the aftermath of the Covid-19 pandemic. The need for adaptation for the application of this model, it is said, is limited because it is limited by new habits with the implementation of health protocols, short learning time, and restrictions on student activities. The adaptation process, one of which is the use of learning media used during learning. The Quizizz application is one of the alternative media that can be used when the system is in the network or directly, because of its flexible nature. Media Quizizz is a tool that can help students and teachers in the learning process. The purpose of this study was to find out the Quizizz application used in Islamic Education (PAI) learning at SMP Negeri 7 Purwokerto Indonesia with a limited face-to-face system. This research uses a qualitative method with a case study approach. Data collection is carried out using observation, interviews, and documentation. The description of the research results was analyzed using Miles and Huberman's model, namely data reduction, data presentation, and conclusion drawing. The author's initial steps formulate the problem. Then collect the necessary data. Next, the researcher analyzed the results of the study. In this study, the authors found that the Quizizz application was used in Islamic Education (PAI) learning as a learning medium. This application becomes a new online-based media that is very flexible and easy to use. The Quizizz application can be used by Islamic Education (PAI) teachers for student learning evaluation, which can be done in the classroom or used as homework, and in online learning systems or limited face-to-face learning systems.